Aktivitas Fisik Generasi Zillenial di Kota Bandung Berdasarkan Gender - Devi, Sri; Damayanti, Imas; Rahayu, Nur Indri; Ruhayati, Yati; Suherman, Adang; Jajat, Jajat; Sultoni, Kuston; Ugelta, Surdiniaty (Institut Teknologi Bandung, 2023)
The purpose of this study was to examine differences in the level of physical activity of zillenial generation based on gender. The method used is a quantitative research method with a comparative causal approach. The population of this study is generation Z who live in Kota Bandung. The sample in this study was 134 people with the sampling technique using Convenience Sampling. The physical activity instrument in data collection uses the Global Physical Activity Questionnaire (GPAQ). Data was analyzed using Mann Whitney U test. The description of the physical activity of the zillenial generation based on the GPAQ domain shows that in the domain of activity at work/study, travel to and from places and sedentary behavior there are no differences based on gender. Which shows that Generation Z does a lot of moderate physical activity. While in the domain of recreational activities there are differences based on gender. The results of the data analysis show the value of sig. p=0.453 > 0.05, data is significant. The results of this study concluded that there was no difference in the physical activity of zillenial generation based on gender.